Improving Learning Outcomes of Elementary School Students by Using Mind Mapping Models with Audio Visual Media: A Classroom Action Research - Irma Silvia; Wati Oviana; Azmil Hasan Lubis (Jurnal Pendidikan Profesi Guru, 2023)
This study aims to determine the increase in learning outcomes of elementary school students with the Mind Mapping model assisted by audio-visual media in thematic learning. This study used a Classroom Action Research (PTK) design with 25 class IVa students as subjects, consisting of 11 boys and 14 girls. This classroom action research procedure includes three cycles and each cycle consists of planning, implementing, observing, and reflecting. The results showed that in the first cycle, students who achieved KKM, namely obtaining a score equal to or more than 73 by 15 students (60%), in cycle II students who achieved KKM, namely obtaining a value equal to or more than 73 by 19 students (76%), whereas in cycle III students who achieved KKM, namely obtaining scores equal to or more than 73 as many as 22 students (88%) and were included in the very good category and had fulfilled classical completeness. Thus, it can be concluded that the application of the mind mapping model with audio visual media can increase teacher activity, student activity and learning outcomes in class IV MIN 26 Aceh Besar.